Induced Pluripotent Stem Cells for Ischemic Stroke Treatment - Duan, Ranran; Gao, Yang; He, Ruya; Jing, Lijun; Li, Yanfei; Gong, Zhe; Yao, Yaobing; Luan, Tingting; Zhang, Chaopeng; Li, Li; Jia, Yanjie (Frontiers in Neuroscience, 2021)
Ischemic stroke is one of the main central nervous system diseases and is associated with high disability and mortality rates. Recombinant tissue plasminogen activator (rt-PA) and mechanical thrombectomy are the optimal therapies available currently to restore blood flow in patients with stroke; however, their limitations are well recognized. Therefore, new treatments are urgently required to overcome these shortcomings. Recently, stem cell transplantation technology, involving the transplantation of induced pluripotent stem cells (iPSCs), has drawn the interest of neuroscientists and is considered to be a promising alternative for ischemic stroke treatment. iPSCs are a class of cells produced by introducing specific transcription factors into somatic cells, and are similar to embryonic stem cells in biological function. Here, we have reviewed the current applications of stem cells with a focus on iPSC therapy in ischemic stroke, including the neuroprotective mechanisms, development constraints, major challenges to overcome, and clinical prospects. Based on the current state of research, we believe that stem cells, especially iPSCs, will pave the way for future stroke treatment.